Regulation of IFN-gamma-induced host cell MHC antigen expression by Kirsten MSV and MLV. II. Effects on class II antigen expression. - Maudsley, D J (1989)
We have reported previously that the Kirsten murine sarcoma virus (Ki-MSV), which carries the v-Ki-ras oncogene, prevents the induction of the class II MHC antigen H-2A and reduces the induction of class I MHC antigens by interferon-gamma (IFN-gamma) on C3H10T 1/2 fibroblasts. It is here shown that the abolition by the virus of H-2A expression extends also to class II antigen H-2E and that this is maintained for at least 7 days after IFN treatment. In addition no concentration of IFN-gamma tested, including supra-optimal concentrations for class I antigen expression, induced class II antigens on MSV-infected cells. Thus MSV inhibits the induction by IFN-gamma of class II MHC antigens by a mechanism other than via a change in kinetics of response to, or in the sensitivity of the cells to, IFN. The possibility that transformation by MSV could result in the (selective) outgrowth of cells unresponsive to IFN was refuted by the observation that clones of C3H10T 1/2, when infected with Ki-MSV, expressed no or dramatically reduced levels of H-2A or H-2E. One C3H10T 1/2 clone chosen for high class II expression, when transformed with Ki-MSV, did express low levels of class II antigens at optimal concentrations of IFN-gamma, suggesting that the degree of the reduction of class II expression varies with the cells that are infected. Comparison with mechanisms whereby other viruses inhibit MHC antigen display revealed an interesting possibility: IFN response sequences (IRS) identified in the virus genomes might act in trans to (down) regulate MHC antigen expression. This could be an important mechanism determining the tumourigenicity of, and immune evasion by, Ki-MSV and other viruses.